Westward Ho! Or, The Voyages and Adventures of Sir Amyas Leigh, Knight, of Burrough, in the County of Devon, in the Reign of Her Most Glorious Majesty Queen Elizabeth - Kingsley, Charles, 1819-1875 (Salt Lake City, UT : Project Gutenberg, 2006)
"Westward Ho! Or, The Voyages and Adventures of Sir Amyas Leigh, Knight, of$1! =(B" by Charles Kingsley is a historical novel published in 1855. Set during Elizabeth I's reign, it follows adventurer Amyas Leigh from Devon to the Caribbean in pursuit of gold and glory. When tragedy strikes$1 (Bhis beloved Rose and brother Frank burned by the Spanish Inquisition$1 (BAmyas vows vengeance against Spain. Through sea battles, romance with an Indian maiden, and defense against the Armada, this patriotic tale celebrates England's Elizabethan triumphs while exploring themes of faith, revenge, and redemption. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Westward_Ho!_(novel)
Release date is 2006-05-14
Produced by Donald Lainson and David Widger
Keywords: Great Britain -- History -- Elizabeth, 1558-1603 -- Fiction